Stability of monascus color in nitrite-cured meat products - Dela Paz, Charity Jaggielyn Espiritu
ABSTRACT The study aimed to evaluate the color stability of Monascus red rice pigment (MRRP) in aqueous solutions (300 and 500 mg/l) as affected by exposure to: light (1200 Lumen), air, pasteurization temperature (62.8°C for 30 min), boiling temperature (maximum of 60 min), thermal sterilization (121.5°C for 15 min) and various pH levels (4-12). Likewise, the color stability of MRRP was evaluated when incorporated in nitrite-cured hotdog and Philippine sweet bacon (tocino) formulations immediately after processing and after 5 freeze-thaw cycles. All experimental challenges significantly affected the stability of MRRP in aqueous solution at 5% level of significance. Color and overall acceptability and color intensity were found to be significantly affected by MRRP incorporation in hotdog and tocino. Baseline studies on the changes in chemistry of MRRP in meat applications were recommended